Semiótica y acción comunicativa : una ruta entre Pierce, Apel y Habermas (2005)
ABSTRACT: The purpose of this article is to review the assertions of Piercian semiotics and its fundamental relation with the communication community of Apel, and Habermas "communicative action". The idea of a society that is connected, constructor of consensus and democratic, has its roots in theories of language and pragmatics. Therefore, it is important to return to its origins and try to find in the questions of these authors some guides for social interlocution.